Ultraviolet-resistant high-reflection polycarbonate film and preparation method thereof
By using modified inorganic filler masterbatch and pre-foamed polycarbonate resin in the light reflective film, combined with blending method and twin-screw extrusion mechanism preparation technology, it is solved that it is difficult for existing light reflective films to achieve high reflectivity and resistance at the same time. The problem of ultraviolet aging has achieved efficient and low-cost high-performance light reflective film preparation.
Patent Information
- Application Number
- CN202411656316.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-21
AI Technical Summary
It is difficult for the existing light reflective film to achieve high reflectivity, heat resistance, aging resistance and UV resistance in liquid crystal backlight modules at the same time, especially the high addition of inorganic nanoparticles leads to material waste and increased costs.
By using the modified inorganic filler masterbatch as a basis for low addition, combining pre-foamed polycarbonate resin, fluorescent dyes and modified inorganic filler masterbatch (such as TiO2-KH570), a blending method and a twin-screw extrusion mechanism are prepared by using the blending method and a twin-screw extrusion mechanism. UV-resistant high reflection polycarbonate film.
With low added amount of inorganic nanoparticles, high reflectivity (up to 99.3%) and excellent UV aging resistance are achieved, while reducing material waste and production costs.
Smart Images

Figure BDA0005142195160000071 
Figure BDA0005142195160000072 
Figure BDA0005142195160000073
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical films, in particular to an ultraviolet-resistant high-reflective polycarbonate film and a preparation method thereof. Background Art
[0002] Light reflective film refers to a type of functional film that can reflect light within a specific wavelength range. Reflectivity is an important indicator for evaluating its performance. In the LCD backlight module, the main function of the reflective film is to reflect as much light as possible from the light source to the light guide plate or diffuser plate, thereby improving pipeline utilization and reducing power consumption. According to the technical requirements of the LCD backlight module, the light reflective film should have high reflectivity, high heat resistance, aging resistance, UV resistance and other properties.
[0003] Generally, light reflective materials are used in displays, signboards, lighting and LCD backlights. Polycarbonate (PC) resin has the characteristics of high heat resistance, good weather resistance and dimensional stability. Compared with the currently used PET and PP substrates, PC reflective film has better heat resistance and weather resistance, and can be exposed to light for a long time in LCD displays without significant changes in performance. In recent years, it has received widespread attention in the field of light reflective films.
[0004] At present, the preparation methods of light reflective materials are generally multilayer film method, microfoaming method and blending method. The multilayer film method refers to a method of preparing a light reflective film by superimposing multiple layers of film structures with different light refractive indices. The main principle is to use the large refractive index difference between the film layers and increase the number of light refractions to achieve the purpose of improving the reflectivity. This method mostly uses sputtering, evaporation or coating processes. The reflective film obtained by this process is costly, difficult to achieve industrialization and large-screen, and the film layers are prone to fall off. The foaming method refers to the addition of a foaming agent or an inert gas during the resin extrusion process. The melt cast from the die contains microbubbles, and a light reflective film is prepared after cooling and molding. The main principle is to use the refractive index difference between the internal pores of the resin and the resin matrix to improve the reflectivity of the reflective film. This method is often combined with a biaxial stretching process. This method is suitable for materials such as polyester, polypropylene, polyamide, polystyrene, etc., but not for materials such as polycarbonate, so there are certain limitations. The blending method refers to blending a resin matrix with inorganic particles with different refractive indices, and preparing a reflective film through processes such as extrusion and stretching. This method is low-cost and simple in process. The production process of PC reflective film mainly uses the blending method, that is, adding inorganic nanoparticles with a high refractive index to the PC substrate to prepare a reflective film with a high reflectivity. However, when using this method to prepare PC reflective film, the amount of inorganic nanoparticles added is relatively high, generally requiring an amount of 25-35wt%. If the amount added is low, the reflectivity of the reflective film is low, which is difficult to meet actual needs. If the amount added is high, the appearance of the reflective film is very poor and wastes materials, increasing costs.
[0005] Based on this, it is extremely important to develop a PC reflective film with low added inorganic particle masterbatch, high reflectivity, excellent aging resistance and good stability. Summary of the invention
[0006] The object of the present invention is to provide a UV-resistant high-reflective polycarbonate film and a preparation method thereof, so as to enable the PC reflective film to achieve high reflectivity and high UV-resistant aging performance on the basis of a low addition amount of modified inorganic filler masterbatch.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A UV-resistant high-reflective polycarbonate film, composed of the following raw materials in percentage by weight:
[0009] 72%-87.5% pre-foamed polycarbonate resin, 10%-20% modified inorganic filler masterbatch, 0.2%-1% antioxidant, 2%-6% fluorescent dye and 0.3%-1% dispersant; wherein the sum of the weight percentages of the various components is 100%.
[0010] The pre-foamed polycarbonate resin is obtained by foaming a polycarbonate resin with a gas foaming agent;
[0011] The modified inorganic filler is obtained by modifying the inorganic filler with a coupling agent.
[0012] As some possible implementation methods of the present application, the UV-resistant high-reflective polycarbonate film is composed of the following raw materials in weight percentage:
[0013] 78%-85% pre-expanded polycarbonate resin, 12%-16% modified inorganic filler masterbatch, 0.2%-0.8% antioxidant, 2%-5% fluorescent dye and 0.3%-1% dispersant;
[0014] As some possible embodiments of the present application, the gas foaming agent is selected from air, nitrogen, carbon dioxide, butane and propane.
[0015] As some possible implementation methods of the present application, the modified inorganic filler is obtained by modifying TiO2 with KH570, that is, the modified inorganic filler is TiO2-KH570.
[0016] As some possible embodiments of the present application, the fluorescent dye is selected from 1,4-diphenylethylene benzene, 4,4-divinyldiphenylethylene, triazine aminodiphenylethylene and 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene; preferably 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene.
[0017] As some possible implementation methods of the present application, the dispersant is polyethylene wax or stearic acid, preferably stearic acid.
[0018] As some possible embodiments of the present application, the antioxidant is selected from tris(2,4-di-tert-butylphenyl) phosphite, n-octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and pentaerythritol stearate; preferably tris(2,4-di-tert-butylphenyl) phosphite.
[0019] In addition, to achieve the above object, the present invention also provides a method for preparing a UV-resistant highly reflective polycarbonate film, comprising the following steps:
[0020] S1. The pre-foamed polycarbonate, the modified inorganic filler masterbatch, the fluorescent dye, the dispersant and the antioxidant are fully mixed to obtain a mixed material;
[0021] S2. The mixed material is added into a single screw extruder, and after high-speed shearing, mixing and conveying, a molten mixture is obtained; thereafter, the mixture is cast, film drawn and cooled to obtain the UV-resistant and highly reflective PC film.
[0022] In this scheme, the gas foaming agent gradually infiltrates into the polycarbonate resin particles under high pressure, and the resin re-enters the normal pressure state. It also takes a while for the infiltrated gas to be completely eliminated. During this period of time, the pre-foamed polycarbonate resin particles containing the gas foaming agent are mixed evenly with the modified inorganic filler masterbatch, fluorescent dye, dispersant, and antioxidant in proportion, and then put into a twin-screw extruder for production. The pre-foamed polycarbonate resin is melted in the twin-screw extruder. Since the pre-foamed polycarbonate resin contains gas, the gas expands due to heat, forming microbubbles in the pre-foamed polycarbonate. The formation of bubbles and the dispersion of the modified inorganic filler masterbatch, fluorescent dye, dispersant, and antioxidant into the molten pre-foamed polycarbonate are carried out simultaneously in the twin-screw extruder. As the twin screws are transported forward to cast the film, it is quickly cooled and shaped in the cooling stage to prepare a UV-resistant and highly reflective PC film. The fluorescent dye added to the formula absorbs invisible ultraviolet light in the light and emits visible blue light; on the other hand, the addition of modified inorganic filler masterbatch enhances the product's absorption of ultraviolet light and can reflect most of the visible light; more importantly, the formation of microbubbles increases the number of reflections of the incident light, thereby improving the reflectivity, and thus obtaining the ultraviolet-resistant and highly reflective polycarbonate.
[0023] As some possible implementation methods of the present application, the temperature of the homogenizing section of the extruder is 275-290° C., the die head temperature is 265-280° C., and the screw speed is 100 rpm-500 rpm.
[0024] As some possible implementation methods of the present application, the preparation method of the pre-foamed polycarbonate is: polycarbonate resin particles are put into an autoclave containing a gas foaming agent for impregnation, the impregnation pressure is 0.2-0.5MPa, the impregnation time is 1-5h, and after the impregnation is completed, the pre-foamed polycarbonate resin is obtained.
[0025] As some possible implementation methods of the present application, the preparation method of the modified inorganic filler masterbatch is as follows:
[0026] An organic solvent, a silane coupling agent and triethylamine are added to the inorganic filler, and then the mixture is fully dispersed in an ice water bath. After the dispersion is completed, the mixture is heated and refluxed. After the reflux is completed, the mixture is vacuum filtered, washed and dried in sequence to obtain the modified inorganic filler. The modified inorganic filler is blended with polycarbonate and added into a twin-screw granulator to obtain a modified inorganic filler masterbatch.
[0027] Wherein, the organic solvent is selected from toluene, xylene, acetone, and ethanol; and the silane coupling agent is selected from KH550, KH560, and KH570.
[0028] As some possible implementation methods of the present application, the preparation method of TiO2-KH570 is as follows:
[0029] (1) Take 10-20 parts of TiO2 powder into a 500 ml four-necked flask, add 55-78 parts of toluene, 10-20 parts of KH570, and 2-5 parts of triethylamine, and disperse by ultrasonic in an ice-water bath;
[0030] (2) Place the four-necked flask in a heating mantle, raise the temperature to 100-120°C, stir mechanically, and reflux for 8 hours;
[0031] (3) After the reaction solution is cooled, vacuum filter it and wash it with acetone several times;
[0032] (4) Extraction in a Soxhlet extractor using toluene as solvent for 3-6 hours to remove organic matter on the surface of the powder that has not undergone chemical reaction, and then washing with acetone;
[0033] (5) Dry in a vacuum oven at 45-80°C for 8-10 h, and grind to obtain TiO2-KH570.
[0034] (6) TiO2-KH570 and polycarbonate are mixed in a ratio of 1:1 and added into a twin-screw granulator to obtain a molten mixture under high-speed shearing of the screw. The molten mixture is drawn into strips and sheared to obtain TiO2-KH570 resin.
[0035] The beneficial effects of the present invention are:
[0036] 1. The present invention improves the raw materials of the polycarbonate film in the prior art and optimizes the usage ratio of each raw material, so that the prepared PC reflective film can achieve high reflectivity (the reflectivity can reach 99.3%) and high resistance to ultraviolet aging on the basis of a low addition amount (≤20wt%) of the modified inorganic filler masterbatch. Specifically, the fluorescent dye added to the raw material absorbs invisible ultraviolet rays in the light and emits visible blue light, which complements the yellow light emitted by the material to form white light. This method improves the reflectivity of the material while improving the resistance to ultraviolet aging. The modified inorganic filler masterbatch (preferably TiO2-KH570) added to the raw material has excellent scattering ability, which causes the light to be reflected multiple times inside the material, increases the propagation path of the light and thus increases the proportion of reflected light. In addition, the modified inorganic filler masterbatch has excellent absorption capacity for ultraviolet rays in the light, so that the product enhances the absorption of ultraviolet light and can reflect most of the visible light, so as to improve the reflectivity of the material while improving the resistance to ultraviolet aging. Pre-foamed polycarbonate is added to the raw material, so that the prepared ultraviolet-resistant high-reflection PC film has two layers of microbubble / polycarbonate interface. When irradiated with light, the incident light can be reflected twice at the two-layer interface, and finally multiple reflections are formed, thereby improving the reflectivity.
[0037] 2. The present invention adopts a blending method to prepare a UV-resistant and highly reflective polycarbonate film, wherein polycarbonate resin particles containing a gas foaming agent are uniformly mixed with modified inorganic filler masterbatch, fluorescent dye, dispersant, and antioxidant in proportion, and then put into a twin-screw extruder for production; the pre-foamed polycarbonate resin is melted in the twin-screw extruder, and since the pre-foamed polycarbonate resin contains gas, the gas expands when heated, and microbubbles are formed in the pre-foamed polycarbonate resin, and the formation of bubbles and the dispersion of modified inorganic filler masterbatch, fluorescent dye, dispersant, and antioxidant into molten polycarbonate are simultaneously carried out in the twin-screw extruder, and the film is cast as the twin screw is conveyed forward, and the film is quickly cooled and shaped in the cooling stage to prepare a UV-resistant and highly reflective PC film. The present invention has a simple preparation process, good controllability, and stable product performance. DETAILED DESCRIPTION
[0038] Example 1
[0039] A method for preparing a UV-resistant high-reflective PC film, the method comprising the following steps:
[0040] S1 prepares pre-foamed polycarbonate resin and TiO2-KH570.
[0041] The method for preparing the pre-foamed polycarbonate resin is as follows: polycarbonate resin particles are put into an autoclave, carbon dioxide is introduced, and the autoclave is impregnated at 0.5 MPa for 2 hours to obtain the pre-foamed polycarbonate resin.
[0042] The preparation method of TiO2-KH570 is as follows:
[0043] (1) Take 15 parts of TiO2 powder and put it into a 500 ml four-necked flask. Add 55-70 parts of toluene, 15 parts of KH570, and 3 parts of triethylamine. Ultrasonic dispersion is carried out in an ice-water bath for 30 minutes.
[0044] (2) Place the four-necked flask in a heating mantle, raise the temperature to 110°C, stir mechanically, and reflux for 7-10 hours.
[0045] (3) After the reaction solution is cooled, it is vacuum filtered and washed with acetone several times.
[0046] (4) Extraction was performed in a Soxhlet extractor using toluene as solvent for 4 h to remove organic matter that did not undergo chemical reaction on the surface of the powder, and then the powder was washed with acetone.
[0047] (5) Dry in a vacuum oven at 80 °C for 8 h, and grind to obtain TiO2-KH570.
[0048] (6) TiO2-KH570 and polycarbonate are mixed in a ratio of 1:1 and added into a twin-screw granulator to obtain a molten mixture under high-speed shearing of the screw. The molten mixture is drawn into strips and sheared to obtain TiO2-KH570 resin.
[0049] S2: 80% pre-expanded polycarbonate resin, 15% TiO2-KH570, 4% 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene, 0.5% stearic acid and 0.5% tris(2,4-di-tert-butylphenyl) phosphite are added into a high-speed mixer and mixed for 10-20 minutes to obtain a mixed material;
[0050] S3 feeds the mixed material into the twin-screw extruder through the feeding device, obtains a molten mixture under the high-speed shearing of the screw, casts the molten mixture into sheets, draws the film, cools, and rolls it up to obtain a UV-resistant and highly reflective PC film. The temperature of the homogenizing section of the extruder is 275-290°C, the die temperature is 265-280°C, and the screw speed is 100rpm-500rpm.
[0051] Example 2
[0052] Compared with Example 1, the carbon dioxide in the method for preparing the pre-expanded polycarbonate resin is replaced by propane, and the remaining steps and parameters are the same as Example 1.
[0053] Example 3
[0054] Compared with Example 1, the carbon dioxide in the method for preparing the pre-expanded polycarbonate resin is replaced by nitrogen, and the remaining steps and parameters are the same as Example 1.
[0055] Example 4
[0056] Compared with Example 1, the amount of pre-expanded polycarbonate resin and TiO2-KH570 in the UV-resistant high-reflection PC film was adjusted, and the amount of each component after adjustment was:
[0057] 75% pre-expanded polycarbonate resin, 20% TiO2-KH570, 4% 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene, 0.5% stearic acid, and 0.5% tris(2,4-di-tert-butylphenyl) phosphite.
[0058] The remaining steps and parameters are the same as in Example 1.
[0059] Example 5
[0060] Compared with Example 1, the amount of pre-expanded polycarbonate resin and TiO2-KH570 in the UV-resistant high-reflection PC film was adjusted, and the amount of each component after adjustment was:
[0061] 85% pre-expanded polycarbonate resin, 10% TiO2-KH570, 4% 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene, 0.5% stearic acid, and 0.5% tris(2,4-di-tert-butylphenyl) phosphite.
[0062] The remaining steps and parameters are the same as in Example 1.
[0063] Example 6
[0064] Compared with Example 1, the impregnation pressure of 0.5 MPa in the preparation method of the pre-foamed polycarbonate resin is replaced with 0.3 MPa, and the remaining steps and parameters are the same as in Example 1.
[0065] Example 7
[0066] Compared with Example 1, the impregnation pressure of 0.5 MPa in the method for preparing the pre-foamed polycarbonate resin is replaced with 0.4 MPa, and the remaining steps and parameters are the same as in Example 1.
[0067] Example 8
[0068] Compared with Example 1, the pre-foaming time of 2 hours in the preparation method of the pre-foamed polycarbonate resin is replaced by 1 hour, and the other steps and parameters are the same as Example 1.
[0069] Example 9
[0070] Compared with Example 1, the pre-foaming time of 2 hours in the method for preparing the pre-foamed polycarbonate resin is replaced by 3 hours, and the remaining steps and parameters are the same as Example 1.
[0071] Example 10
[0072] Compared with Example 1, the amount of pre-expanded polycarbonate resin and 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene in the UV-resistant high-reflection PC film was adjusted, and the amount of each component after adjustment was:
[0073] 80% pre-expanded polycarbonate resin, 15% TiO2-KH570, 2% 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene, 0.5% stearic acid, and 0.5% tris(2,4-di-tert-butylphenyl) phosphite.
[0074] Embodiment 11
[0075] Compared with Example 1, the amount of pre-expanded polycarbonate resin and 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene in the UV-resistant high-reflection PC film was adjusted, and the amount of each component after adjustment was:
[0076] 80% pre-expanded polycarbonate resin, 15% TiO2-KH570, 6% 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene, 0.5% stearic acid, and 0.5% tris(2,4-di-tert-butylphenyl) phosphite.
[0077] Example 12
[0078] Compared with Example 1, the pre-foamed polycarbonate resin is replaced by polycarbonate resin, and the remaining steps and parameters are the same as Example 1.
[0079] Embodiment 13
[0080] Compared with Example 1, the pre-foamed polycarbonate resin was replaced with a polycarbonate resin, 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene was not added, and the amounts of polycarbonate and TiO2-KH570 were adjusted. After adjustment, the amounts of each component were:
[0081] 84% polycarbonate resin, 15% TiO2-KH570, 0.5% stearic acid, 0.5% tris(2,4-di-tert-butylphenyl) phosphite.
[0082] Embodiment 14
[0083] Compared with Example 1, the pre-foamed polycarbonate resin was replaced with a polycarbonate resin, 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene was not added, and the amounts of polycarbonate and TiO2-KH570 were adjusted. After adjustment, the amounts of each component were:
[0084] 74% polycarbonate resin, 25% TiO2-KH570, 0.5% stearic acid, 0.5% tris(2,4-di-tert-butylphenyl) phosphite.
[0085] Embodiment 15
[0086] Compared with Example 1, the pre-foamed polycarbonate resin was replaced with a polycarbonate resin, 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene was not added, and the amounts of polycarbonate and TiO2-KH570 were adjusted. After adjustment, the amounts of each component were:
[0087] 64% polycarbonate resin, 35% TiO2-KH570, 0.5% stearic acid, 0.5% tris(2,4-di-tert-butylphenyl) phosphite.
[0088] The reflectivity of the UV-resistant and highly reflective PC films in Examples 1-3 and the effect of the type of gas foaming agent on the reflectivity of the UV-resistant and highly reflective PC films are shown in Table 1.
[0089] Table 1:
[0090]
[0091] The reflectivity of the UV-resistant high-reflection PC films in Examples 1, 4 and 5, and the effects of the amounts of pre-foamed polycarbonate resin and TiO2-KH570 on the reflectivity of the UV-resistant high-reflection PC films are shown in Table 2.
[0092] Table 2:
[0093]
[0094] The reflectance of the UV-resistant and highly reflective PC films in Examples 1, 6 and 7, and the effect of the pre-foaming and impregnation pressure on the reflectance of the UV-resistant and highly reflective PC films are shown in Table 3.
[0095] Table 3:
[0096]
[0097] The reflectivity of the UV-resistant and highly reflective PC films in Examples 1, 8 and 9, and the effect of the pre-foaming and impregnation time on the reflectivity of the UV-resistant and highly reflective PC films are shown in Table 4.
[0098] Table 4:
[0099]
[0100]
[0101] The reflectance of the UV-resistant and highly reflective PC films in Examples 1, 10 and 11, and the effects of the amounts of pre-foamed polycarbonate resin and fluorescent dye on the reflectance of the UV-resistant and highly reflective PC films are shown in Table 5.
[0102] Table 5:
[0103]
[0104] The reflectivity in Examples 1 and 12, and the effects of pre-foamed polycarbonate resin and polycarbonate resin on the reflectivity of the PC film are shown in Table 6.
[0105] Table 6:
[0106]
[0107] Among them, the reflectivity in Examples 13, 14 and 15, and the effects of inorganic filler masterbatch and polycarbonate resin on the reflectivity of the PC film are shown in Table 7.
[0108] Table 7:
[0109]
[0110]
[0111] Furthermore, the samples of Example 1 and Example 13 were placed in a UV aging box for UV resistance testing with an irradiance of 200 W / m2. Samples were taken after 24 h, 48 h, and 72 h to test the reflectivity. The test results are shown in Table 8.
[0112] Table 8:
[0113]
[0114] The samples of Example 1 and Example 13 were placed in a wet heat aging oven for aging tests. After 24 h, 48 h, 72 h, 96 h, 120 h, 144 h, and 168 h, samples were taken to test the reflectivity. The test results are shown in Table 9.
[0115] Table 9:
[0116]
[0117] From Table 1 to Table 9, we can see that:
[0118] 1. Pre-foamed polycarbonate resin particles are mixed with modified inorganic filler masterbatch, fluorescent dye, dispersant and antioxidant in the ratio set by the present invention, and the mixture is put into a twin-screw extruder to produce a UV-resistant high-reflective PC film with a reflectivity of not less than 94.2%, and even up to 99.3%. The PC reflective film has a high reflectivity on the basis of a low addition amount (≤20wt%) of the modified inorganic filler masterbatch, and the UV aging test (200W / m 2After 72 hours of aging, the reflectivity of the material has almost no significant change, achieving the purpose of UV aging resistance. After 168 hours of wet heat aging test (85°C, 85%), the reflectivity of the material is still maintained above 95%, indicating that the UV-resistant high-reflective PC film has excellent stability in real complex use environments.
[0119] 2. The type of pre-foaming foaming agent, impregnation time, impregnation pressure, pre-foaming resin content, modified inorganic filler masterbatch content, and fluorescent dye content have a significant effect on the reflectivity of the UV-resistant PC film material. The reason may be that these factors affect the size and number of pores produced by foaming, as well as the content of inorganic seasonings and fluorescent dyes on the reflectivity, which ultimately affects the reflection effect. The present invention prepares a UV-resistant and highly reflective polycarbonate film by blending and extruding a pre-foaming resin with a modified inorganic filler, a fluorescent dye, a dispersant, and an antioxidant. It can be seen from the above examples that the reflective PC prepared in this way has the advantages of high reflectivity, excellent UV aging resistance, low production cost, and low equipment requirements.
Claims
1. A UV-resistant highly reflective polycarbonate film, characterized in that: It is composed of the following raw materials in weight percentage: 72%-87.5% pre-expanded polycarbonate resin, 10%-20% modified inorganic filler, 0.2%-1% antioxidant, 2%-6% fluorescent dye and 0.3%-1% dispersant; The pre-foamed polycarbonate resin is obtained by foaming a polycarbonate resin with a gas foaming agent; The modified inorganic filler is obtained by modifying the inorganic filler with a coupling agent.
2. The UV-resistant highly reflective polycarbonate film according to claim 1, characterized in that: It is composed of the following raw materials in weight percentage: 78%-85% pre-foamed polycarbonate resin, 12%-16% modified inorganic filler masterbatch, 0.2%-0.8% antioxidant, 2%-5% fluorescent dye and 0.3%-1% dispersant.
3. The UV-resistant highly reflective polycarbonate film according to claim 1, characterized in that: The gas blowing agent is selected from the group consisting of air, nitrogen, carbon dioxide, butane and propane.
4. The ultraviolet-resistant highly reflective polycarbonate film according to claim 1, characterized in that: The modified inorganic filler masterbatch is obtained by modifying TiO2 with KH570.
5. The ultraviolet-resistant highly reflective polycarbonate film according to claim 1, characterized in that: The fluorescent dye is selected from 1,4-diphenylethylene benzene, 4,4 divinyl diphenylethylene, triazine amino diphenylethylene and 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene.
6. The UV-resistant high-reflection PC film according to claim 1, characterized in that: The antioxidant is selected from tris(2,4-di-tert-butylphenyl)phosphite, n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and pentaerythritol stearate.
7. The method for preparing a UV-resistant highly reflective polycarbonate film according to any one of claims 1 to 6, characterized in that: The steps include: S1. The pre-foamed polycarbonate, the modified inorganic filler masterbatch, the fluorescent dye, the dispersant and the antioxidant are fully mixed to obtain a mixed material; S2. The mixed material is added into a single screw extruder, and after high-speed shearing, mixing and conveying, a molten mixture is obtained; thereafter, the mixture is cast, film drawn and cooled to obtain the UV-resistant and highly reflective PC film.
8. The method for preparing a UV-resistant highly reflective polycarbonate film according to claim 7, characterized in that: The temperature of the homogenizing section of the extruder is 275-290°C, the die head temperature is 265-280°C, and the screw speed is 100rpm-500rpm.
9. The method for preparing a UV-resistant highly reflective polycarbonate film according to claim 7, characterized in that: The preparation method of the pre-foamed polycarbonate comprises: putting polycarbonate resin particles into an autoclave containing a gas foaming agent for impregnation, the impregnation pressure is 0.2-0.5 MPa, the impregnation time is 1-5 hours, and after the impregnation is completed, the pre-foamed polycarbonate resin is obtained.
10. The method for preparing a UV-resistant highly reflective polycarbonate film according to claim 7, characterized in that: The preparation method of the modified inorganic filler masterbatch is as follows: An organic solvent, a silane coupling agent and triethylamine are added to the inorganic filler, and then the mixture is fully dispersed in an ice water bath. After the dispersion is completed, the mixture is heated and refluxed. After the reflux is completed, the mixture is vacuum filtered, washed and dried in sequence to obtain the modified inorganic filler. The modified inorganic filler is blended with polycarbonate and added into a twin-screw granulator to obtain a modified inorganic filler masterbatch.